Angular differences between the lower extremity and the ground that express maximum core muscle activation according to core-strengthening exercises - Son, N. J.; Jun, H. J.; Yi, K. O. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to investigate the maximum core muscle activation angle according to core-strengthening exercises. Method: Twenty-six young female football players (age: 17.84 ± 0.80 years, height: 163.08 ± 5.25 cm, weight: 54.96 ± 7.41 kg) registered in the Korea Football Association from D High School located in Seoul were the subjects of this research. An electromyogram (Noraxon, USA) was used for monitoring the maximum core muscle contraction activity. Results: The angle for the maximum core muscle strength per core exercise and muscle was the smallest for the upper rectus abdominis in the windshield wiper exercise. The angle of the vastus medialis was significantly the largest. The range of angles at which the maximum strength was observed for each core exercise were as follows: 1) abdominal flutter kicks (11~40°), 2) leg raises (21~34°), 3) scissors (45~66°), 4) knee to elbow sit-ups (42~64°), 5) reverse crunches (9~40°), 6) butt-ups (24~32°), 7) V sit-ups (5~24°), 8) windshield wipers (11~20°), 9) bird dog (11~18°), and 10) raised leg plank (38~50°). Conclusion: Four kinds of motion could be classified according to the range of angles at which the core muscles were maximally activated. The first group involves the range of motion that gives the maximum muscle strength when the lower extremity and ground angle was between 5° and 24°, such as the V sit-ups, windshield wipers, and bird dog. The second group comprised the flutter kicks and reverse crunches at an angle between 9° and 40°. The third group comprised the leg raise and butt-up exercises at an angle between 21° and 34°. The fourth group included the scissors, knee to elbow sit-ups, and raised leg plank at an angle between 38° and 66°. These results may be useful as basic data for core movement and core muscle training according to the purpose of exercise.